THE EFFECT OF ELECTRONIC WORD OF MOUTH (EWOM), PRODUCT QUALITY AND PRICE ON PURCHASE DECISIONS - Didin Hikmah Perkasa; Indri Astiana Suhendar; Vely Randyantini; Evelina Andrini M (Dinasti Publisher, 2020)
This study aims to determine the effect of E-Wom (Electronical World of Mouth), Product Quality and Price on Purchasing Decisions The type of research used in this study is descriptive associative using a causal approach. The population in this study are Xiaomi consumers who have purchased Xiaomi mobile phones. The sampling technique used is non-probability sampling and the type of sampling used is purposive sampling. The method of data collection using questionnaire and analysis technique using SEM (Structural Equational Modeling) wherein there is an inner model and outer model test and the tools used are SmartPLS 3.0. Data collection techniques using questionnaires that have been tested for validity and reliability. The results showed that partially electronic variable word of mouth, product quality and price had a positive and significant effect on purchasing decisions.